Upgrading Students’ Vocabularies Using SMS (Semantic Mapping Strategy) in Post Pandemic Era - Ayu Fitrianingsih (Jurnal Pendidikan Edutama, 2023)
Abstract: In the post pandemic era, the students are supposed to have better knowledge. Many of them got learning loss because of distance learning (Engzell, Frey, & Verhagen, 2021). This study aims to upgrade the students’ vocabularies using semantic mapping strategy (SMS). This classroom action research was conducted to the seventh grade students of SMP Plus Al hidayah Parengan. The data is collected using test, observation, and interview. The results of study reveal that the average of students’ scores who pass the grade in pre-test is 30%. In cycle 1, it increases into 50%. It is more increased in cycle II in which the average of students’ scores who pass the grade is 90%. It can be concluded that the semantic mapping strategy is able to upgrade the students’ vocabulary mastery especially in post pandemic era.  Keywords: Students’ Vocabulary, Semantic Mapping Strategy, Post Pandemic Era  Abstrak: Pada masa setelah pandemi usai, siswa diharapkan memiliki pengetahuan yang jauh lebih baik. Menurut pendapat Engzell, Frey, dan Verhagen (2021), kebanyakan dari siswa tersebut mengalami ‘learning loss’ atau kerugian belajar. Oleh sebab itu, penelitian ini bertujuan untuk meningkatkan penguasaan kosakata siswa dengan menggunakan strategi pemetaan semantik/semantic mapping strategy. Penelitian tindakan kelas ini dilakukan pada siswa kelas 7 di SMP Plus Al Hidayah Parengan. Data didapatkan melalui tes, observasi, dan interview. Hasil penelitian menunjukkan bahwa rata-rata nilai siswa yang melampaui batas ketuntasan sebanyak 30%. Pada siklus I, terjadi peningkatan nilai rata-rata siswa yang melampaui batas ketuntasan sebanyak 50%. Hal ini juga terjadi pada siklus II dimana rata-rata nya menjadi 90%. Berdasarkan hasil tersebut, dapat disimpulkan bahwa strategi pemetaan semantic mampu meningkatkan penguasaan kosakata siswa terutama di masa setelah pandemic ini.  Kata Kunci: Kosakata Siswa, Strategi Pemetaan Semantik, Pasca Pandemi